Electrochemical Behaviour and Interfacial Contact Resistance ofTi-6Al-4V and SUS 316L plates with Potential Application as a Bipolar Plate in PEMFC / Nur Fawwaz Asri ...[et al.] - Asri, Nur Fawwaz; Husaini, T.; Majlan, Edy Herianto; Sulong, Abu Bakar; Wan Daud, Wan Ramli (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The main aim of this study is to investigate the corrosion of Ti-6Al-4V and SUS 316L plates as application at anode and cathode condition in PEMFC. The criteria for both current density (<1 μA cm−2) and interfacial contact resistance (<10 mΩ cm2) must meet the DOE's 2020 technical targets. In approaching a lightweight and ease of manufacture bipolar plates, both selected materials were chosen based on their good and relatively low cost factor compared to graphite. Corrosion resistance were observed for both plates as preparation for long-term operations in PEMFC. Potentiostatic test measurements were carried out at room temperature in a solution of 0.5 M H2SO4 with a scan rate 10 mV/s for 10 hours. The result shows good performance of SUS 316L corrosion resistance as compared to Ti-6Al-4V, but it still does not achieve the DOE target. To provide high corrosion resistance at cathode as well as increasing electrical conductivity at anode in PEMFC components, Cr was proposed as surface modification on plates. The current density and ICR decreased to 0.1 μA cm−2 and 17.6 mΩ cm2 for 12 hours immersed during potentiostatic test. Surface modification using PVD magnetron sputtering with 150 W and 80 minutes of deposition was successfully deposited and potentially as bipolar plates in PEMFC application.